PENGARUH PENGADOPSIAN IFRS DAN GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2013) - Ulian Febriansyah Dalimunthe; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This research aims to examine the effect of IFRS adoption and good corporate governance on earnings quality. Adoption of IFRS is measured by dummy variable. The proxy of good corporate governance are audit committee, independent commisoner, institutional ownership, and managerial ownership. The dependent variable in this research is quality earnings measured by discretionary accrual using modified Jones to detect earning management. The population in this research are all of manufacturing companies listed in Indonesia Stock Exchange in 2010-2013. The sampling method in this research uses purposive sampling method. The analytical method in this research is regression analysis after tested by classical assumption tests. The results of this research find that IFRS adoption has significantly positive effect on earnings quality. IFRS adoption can increase earnings quality. Other independent variables i.e. audit committe, independent commisoner, institutional ownership, and managerial ownership have no significantly effect on earnings quality.